PENGARUH KOMUNIKASI ORGANISASI DAN KOMUNIKASI ANTAR PRIBADI TERHADAP KEAKTIFAN PENGURUS GERAKAN PEMUDA ANSOR CABANG TRENGGALEK - Zidni ‘Ilman Nafi’a; Abdul Muhid (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2021)
This study aims to describe the phenomenon of the influence of organizational communication as a basis for organizing and interpersonal communication on the activeness of the Ansor youth committee in Trenggalek Branch. The Ansor youth movement is a socio-religious organization, which has an organizational structure from the center to the regions, the central means at the center of government located in Jakarta and the regions down to the village level which have a considerable share of the changes in the Trenggalek Muslim community. The growing number of organizational members requires a series of coordination and consolidation between members so that this organization works according to its vision and mission. This study uses a quantitative research approach. There are 37 administrators consisting of daily administrators, institutions and departments as samples in the study. The questionnaire is used as a data collection tool. Data analysis using multiple linear analysis. Where, Y = 5,167 + 0,315.X 1 + 0,412.X2. The results of data analysis and hypothesis testing show that there is an influence of organizational communication on the increase in member performance, with an influence of 0.678 where the variable relationship between organizational communication and interpersonal communication has an effect on the performance of the management by 67.8%. Organizational communication has an effect on improving the performance of GP members. Ansor. The results also show that there is an influence of organizational communication and interpersonal communication influencing the activeness of the board and members of the Trenggalek branch of the Ansor youth movement organization. GP organization capabilities. Ansor involves members on organizational issues and translates them into certain forms of action under clear leadership to make the performance of the members more focused and orderly so that members are able to create and handle relationships between others if problems occur. Even the increased organizational spirit enables members to make decisions even in ambiguous and uncertain situations. Openness in building communication is one of the keys to building mutual trust and understanding among Ansor members.